Homo and Hetero Molecular 3D Nanographenes Employing a Cyclooctatetraene Scaffold - Urieta-Mora, Javier; Krug, Marcel; Alex, Wiebke; Perles, Josefina; Fernández, Israel; Molina-Ontoria, Agustín; Guldi, Dirk Michael; Martín, Nazario (Journal of the American Chemical Society, 2020)
Two novel homo and hetero three-dimensional nanographenes, NG1 and NG2, featuring a cyclooctatetraene core are designed, synthesized, and characterized. A concise and efficient bottom-up methodology was employed during which 24 new carbon-carbon bonds were formed. By means of a Scholl reaction nanographenes with 53 fused rings are realized, which exhibited good solubility in common organic solvents. The resulting saddle-like structures of NG1 and NG2 are electron-rich and show good chemical and electrochemical stability. Their molecular structures are fully elucidated by single-crystal X-ray crystallography. From their crystal structure analysis is concluded that both nanographenes are chiral and crystallize as a racemic mixture. Our work was rounded-off by excited state investigations such as electron and energy transfer with electron-acceptors and -donors.
CRIS-Team Scopus Importer:2020-03-17